Sleep procrastination. Causes and consequences of postponed sleep - POHORILSKA, Natalia; KARYBINA, Alyona (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. This article explores the phenomenon of sleep procrastination, which involves consciously or unconsciously delaying sleep to continue engaging in other activities unrelated to sleep disruption. The importance of this study stems from the widespread occurrence os sleep procrastination and its adverse effects on physical and mental health. The study aimed to understand the nature of sleep procrastination, its causes, and its consequences. Methods. The research employed theoretical approaches (analysis, synthesis, literature review) and empirical methods, including K. Lei's General Procrastination Scale, A. Zverkov and E. Eidman's Study of Volitional Self-Regulation, the Epworth Sleepiness Scale, the Pittsburgh Sleep Quality Inventory (PSQI), and the adapted Floor Kroese Sleep Procrastination Scale. The sample consisted of 163 participants aged 14-70 years from various professions.Results. Correlation analysis revealed a positive correlation between sleep procrastination and overall procrastination, sleepiness, deterioration in subjective sleep quality, increased sleep latency, decreased sleep duration, sleep disturbances, and impaired daytime functioning. Controversially, a negative correlation was found between sleep procrastination and volitional self-regulation, perseverance, and self-control. General procrastination also correlated positively with sleepiness, poor sleep quality, sleep latency, sleep disturbances, and daytime functioning, and negatively with volitional self-regulation, perseverance, and self-control. Additionally, voluntary self-regulation, persistence, and self-control were negatively associated with sleep disturbance indicators. The study also identified the influence of age on specific aspects of sleep quality. Regression analysis indicated that sleep procrastination is affected by general procrastination, subjective assessment of sleep quality, sleep duration, and volitional self-regulation.Conclusions. The findings confirm a link between sleep procrastination, low self-regulation, and general procrastination. Sleep procrastination has a detrimental impact on sleep quality, daytime functioning, and overall well-being. However, despite these findings, the regression model is not yet sufficiently robust to accurately predict sleep procrastination, highlighting the need for further research with a larger sample size and consideration of additional factors.
Keywords: sleep procrastination; self-regulation; sleep quality; sleepiness; sleep latency; sleep duration; overall procrastination